2010
DOI: 10.1016/j.envint.2009.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of olestra on the absorption, excretion and storage of 2,2′,5,5′ tetrachlorobiphenyl; 3,3′,4,4′ tetrachlorobiphenyl; and perfluorooctanoic acid

Abstract: Mice were gavaged with either 14C-labeled 2,2’5,5’ tetrachlorobiphenyl; 3,3’,4,4’ tetrachlorobiphenyl; or perfluorooctanoic acid. Absorption of these compounds was determined by assay of feces collected for 48 hours after the gavage. Part of the animals received test diets containing olestra during this 48-hour period to determine its effect on absorption of the compounds. Mice that received the diet without olestra during this period were divided into groups that either continued the diet without olestra or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Recent research has shown that nutritional intervention that promotes a diet rich in antioxidants as well as a healthy lifestyle can help modulate the toxic effects of many of the environmental pollutants present in the human body, including PCBs (Baker et al 2013, Han et al 2012, Newsome et al 2014, Petriello et al 2014a, Petriello et al 2014b). Also, certain dietary fats may decrease overall body burdens by increasing excretion rates (Jandacek et al 2014, Jandacek et al 2010). Finally, novel evidence now implicates exercise as a mediator of pro-inflammatory pollutants such as PCBs and deserves increased investigation as a modulator of environmental pollutant-induced disease (Murphy et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that nutritional intervention that promotes a diet rich in antioxidants as well as a healthy lifestyle can help modulate the toxic effects of many of the environmental pollutants present in the human body, including PCBs (Baker et al 2013, Han et al 2012, Newsome et al 2014, Petriello et al 2014a, Petriello et al 2014b). Also, certain dietary fats may decrease overall body burdens by increasing excretion rates (Jandacek et al 2014, Jandacek et al 2010). Finally, novel evidence now implicates exercise as a mediator of pro-inflammatory pollutants such as PCBs and deserves increased investigation as a modulator of environmental pollutant-induced disease (Murphy et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional intervention, such as with olestra, can interfere with the absorption of dietary PCBs and has been shown to result in their reduced systemic accumulation (Jandacek, Rider, Keller, & Tso, 2010). Similar to such nutritional intervention that suggests modification of enterohepatic circulation or reduced re-absorption of organochlorine compounds (Jandacek &Genuis 2013), PCBs and their metabolites may undergo enhanced enterohepatic circulation during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been undertaken to ameliorate the adverse effects of halogenated biphenyls with dietary interventions, for example with fat substitutes like olestra (Jandacek et al , 2010), minerals like selenium (Stemm et al , 2008; Lai et al , 2011) and manganese (Wang, submitted), various antioxidants (Robertson et al , 1983; Tharappel et al , 2008), or phytochemicals (Glauert et al , 2008). Generally these dietary manipulations resulted in only marginal success.…”
Section: Introductionmentioning
confidence: 99%